Design of Ecological Land Remediation Planning and Remediation Mode Based on Spatial Clustering Algorithm - Yao, Yuzhuo (Informatica (Ljubljana), 2023)
In this article a method is proposed based on a spatial clustering algorithm, in order to better realize the design of ecological land consolidation planning and regulation mode. Considering the GIS methods such as spatial clustering algorithm and least resistance model, the proposed model selects typical projects and put forward ecological land consolidation planning scheme. The unified engineering construction forms and rigid engineering construction standards aims at regularization and rigidization of traditional land consolidation by means of high-intensity engineering construction. Although in the process of stabilizing the amount of cultivated land and improving agricultural production conditions, played a positive role. However, under the current requirements of ecological civilization construction, there is an urgent need for transformation. Through the improvement of ecological land, the ecological improvement is realized, and the need for landscape improvement is foremost requirement. The study is guided by the theory of landscape ecology, according to the general idea of "landscape pattern evaluation-land remediation function zoning-corridor pattern optimization-patch matrix optimization". The experimental results are generated using Fragstates software for calculating various indicators. The results show that, before and after renovation, the landscape types with the largest landscape ecological security index LESi were all cultivated land, and the smallest one was forest land. Except for the river landscape ecological security index, which dropped by 9.84%, the ecological security of other types of landscapes improved. Among them, the largest increase was road (121.29%), followed by forest land (43.10%). According to formulas (1) and (2), the landscape safety index LES of the project area is 0.45 before the renovation, and 0.61 after the renovation. An increase of 35.56% is observed which shows that through the ecological land consolidation project area, the overall landscape ecological security status has been improved. It is proved that the spatial clustering algorithm can better realize the design of ecological land remediation planning and remediation mode.